2014
DOI: 10.1155/2014/484161
|View full text |Cite
|
Sign up to set email alerts
|

Merit of Ginseng in the Treatment of Heart Failure in Type 1-Like Diabetic Rats

Abstract: The present study investigated the merit of ginseng in the improvement of heart failure in diabetic rats and the role of peroxisome proliferator-activated receptors δ (PPARδ). We used streptozotocin-induced diabetic rat (STZ-rat) to screen the effects of ginseng on cardiac performance and PPARδ expression. Changes of body weight, water intake, and food intake were compared in three groups of age-matched rats; the normal control (Wistar rats) received vehicle, STZ-rats received vehicle and ginseng-treated STZ-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Activation of PPARδ by an agonist may improve phenylephrine-induced hypertrophy in cardiomyocytes [ 39 ]. Furthermore, ginseng has been demonstrated to improve heart function via PPARδ in diabetic rats [ 21 ]. In the present study, PPARδ is substantially reduced in the hearts of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of PPARδ by an agonist may improve phenylephrine-induced hypertrophy in cardiomyocytes [ 39 ]. Furthermore, ginseng has been demonstrated to improve heart function via PPARδ in diabetic rats [ 21 ]. In the present study, PPARδ is substantially reduced in the hearts of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Rh2 may also attenuate hyperglycemia in diabetic rats [ 20 ]. Moreover, ginseng has been documented to improve heart function via PPARδ in diabetic rats [ 21 ]. Recently, the activation of PPARδ has been demonstrated to attenuate STAT3 expression [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. ginseng also increased expression of peroxisome proliferator-activated receptor (PPAR) δ in the hearts of DM rats. Therefore, Tsai and colleagues suggested that P. ginseng could improve heart failure by increasing PPAR δ activity in DM rats [6]. In a rat model with ligation of coronary arteries, P. ginseng reversed cardiac hypertrophy, myocardial remodeling, and heart failure by inhibition of calcineurin activation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ginseng is useful to enhance cardiac contractility in animals [ 27 ]. Recently, ginseng has been garnering increasing interest in its effects on the cardiovascular system and in the treatment of heart failure [ 28 ]. Ginsenosides, the effective component of ginseng, regulates cardiovascular function on cardiomyocyte contraction, which may be mediated in part through increased NO production [ 29 ].…”
Section: Discussionmentioning
confidence: 99%